Super (a,d)-H-Antimagic Total Covering pada Graf Semi Windmill - Wuni, Sherly Citra; Agustin, Ika Hesti; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph $G(V,E)$ has a $\mathcal{H}$-covering if every edge in $E$ belongs to a subgraph of $G$ isomorphic to $\mathcal{H}$. An $(a,d)$-$\mathcal{H}$-antimagic total covering is a total labeling $λ$ from $V(G)\cup E(G)$ onto the integers $\{1,2,3,...,|V(G)\cup E(G)|\}$ with the property that, for every subgraph $A$ of $G$ isomorphic to $\mathcal{H}$ the $\sum{A}=\sum_{v\in{V(A)}}λ{(v)}+\sum_{e\in{E(A)}}λ{(e)}$ forms an arithmetic sequence. A graph that admits such a labeling is called an $(a,d)$-$\mathcal{H}$-antimagic total covering. Inaddition, if $\{λ{(v)}\}_{v\in{V}}=\{1,...,|V|\}$, then thegraph is called $\mathcal{H}$-super antimagic graph. In this paperwe study of Shackle of Semi {\it Windmill}